Computing decomposable multigroup indices of segregation. (September 2022) - Guinea-Martin, Daniel; Mora, Ricardo
Eight multigroup segregation indices are decomposable into a between and a within term. They are two versions of 1) the mutual information index, 2) the symmetric Atkinson index, 3) the relative diversity index, and 4) Theil's H index. In this article, we present the commanddseg, which obtains all of them. It contributes to the stock of segregation commands in Stata by 1) implementing the decomposition in a single call, 2) providing the weights and local indices used in the computation of the within term, 3) facilitating the deployment of the decomposability properties of the eight indices in complex scenarios that demand tailor-made solutions, and 4) leveraging sample data with bootstrapping and approximate randomization tests. We analyze 2017 census data of public schools in the United States to illustrate the use ofdseg . The subject topic is school racial segregation.